2016
DOI: 10.1002/jcla.22044
|View full text |Cite
|
Sign up to set email alerts
|

Detection of New Delhi Metallo-Beta-Lactamase (Encoded byblaNDM-1) inEnterobacter aerogenesin China

Abstract: It is important to mandate prudent usage of antibiotics and implement infection control measures to control the spread of these resistant bla -positive strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
4
2
Order By: Relevance
“…The most common and unequivocal carbapenem resistance mechanism of Enterobacterales involves the production of carbapenemases and this study indicated that NDM-5 was the common carbapenemase in CRKA strains, which was different from other reports conducted in other countries ( 3 , 11 ). Notably, the detection rate for NDM type carrying Enterobacterales has risen in recent years.…”
Section: Discussioncontrasting
confidence: 99%
“…The most common and unequivocal carbapenem resistance mechanism of Enterobacterales involves the production of carbapenemases and this study indicated that NDM-5 was the common carbapenemase in CRKA strains, which was different from other reports conducted in other countries ( 3 , 11 ). Notably, the detection rate for NDM type carrying Enterobacterales has risen in recent years.…”
Section: Discussioncontrasting
confidence: 99%
“…A nationwide surveillance study of clinical CRE isolates in China from June 2014 to June 2015 indicated that 1.2 to 18.9% of K. pneumoniae isolates were resistant to carbapenems (20). In the current study, the overall prevalence of CRKP (36.2%) among the K. pneumoniae isolates and the prevalence of CRE (18.1%) among the Enterobacteriaceae isolates between 2014 and 2016 were much higher than those recorded by previous reports from the same area (8,(20)(21)(22). Previous studies have indicated that CRE infections are associated with poor treatment outcomes (23).…”
Section: Discussioncontrasting
confidence: 70%
“…It can be used in both human and veterinary medicine; therefore, a large amount of antibiotics have been released into the environment. The blaNDM-1 gene is resistant to metallo-ß-lactamase and can degrade most antibiotics, including cephalosporins, penicillins, carbapenems and other ß-lactam antibiotics, leading to widespread antibiotic resistance [32]. The blaTEM gene is located on a mobile binding plasmid and transposon, enabling it to be transferred between different species.…”
Section: Absolute Abundance Of Argsmentioning
confidence: 99%